The interface between transcriptional and epigenetic control of effector and memory CD8+ T‐cell differentiation. Issue 1 (September 2014) - Gray, Simon M.; Kaech, Susan M.; Staron, Matthew M.
Summary: Immunity to many intracellular pathogens requires the proliferation, differentiation, and function of CD8 + cytotoxic T lymphocytes (CTLs). While the majority of effector CTLs die upon clearance of the pathogen, a small proportion of them survive to become long‐lived memory CTLs. Memory CTLs can provide protective immunity against re‐exposure to the same pathogen and are the principle motivation behind T‐cell‐ based vaccine design. While a large body of cellular immunologic research has proven invaluable to define effector and memory CTLs by their different phenotypes and functions, an emerging focus in the field has been to understand how environmental cues regulate CTL differentiation on a genomic level. Genome‐wide studies to profile transcriptional and epigenetic changes during infection have revealed that dynamic changes in DNA methylation patterns and histone modifications accompany transcriptional signatures that define and regulate CTL differentiation states. In this review, we emphasize the importance of epigenetic regulation of CD8 + T‐cell differentiation and the likely role that transcription factors play in this process.